The Role of Islamic Social Capital in Promoting Women’s Empowerment for Community Economic Growth - Sinulingga, Nabila Oktarina; Syahriza, Rahmi; Harahap, Muhammad Ikhsan (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
This study investigates the role of Islamic Social Capital, particularly ukhuwah (brotherhood), in group-based financing programs and its impact on women's empowerment and community economic improvement within the Pokmas Mandiri Producer Cooperative at the Serdang Bedagai Branch. Utilizing a qualitative descriptive approach, data were gathered through in-depth interviews, participant observation, and document analysis. Study participants included cooperative administrators, managers, employees, and group members who received financing support. Findings reveal that Islamic social capital—especially trust and ukhuwah—plays a crucial role in empowering economically disadvantaged women who operate micro-businesses. The sense of brotherhood cultivated among group members fosters mutual support during financial challenges, enabling micro-business growth. According to Masudul Alam Choudhury, brotherhood is a principle that creates strong social bonds, which are essential for achieving social justice and collective well-being within the community. This sense of brotherhood within the financing groups reinforces social cohesion and collective action, vital for economic and social development. Furthermore, group-based financing programs effectively enhance the economic stability of member households, as evidenced by increased income and improved capacity to meet basic needs. The application of Islamic social capital also contributes positively to emotional well-being and social harmony, fostering a sense of peace and prosperity within the community.